2017
DOI: 10.1194/jlr.m075879
|View full text |Cite
|
Sign up to set email alerts
|

Dietary PUFAs attenuate NLRP3 inflammasome activation via enhancing macrophage autophagy

Abstract: Dietary PUFAs reduce atherosclerosis and macrophage inflammation, but how nucleotide-binding oligomerization domain leucine-rich repeat-containing receptor protein (NLRP3) inflammasome activation and autophagy influence PUFA-mediated atheroprotection is poorly understood. We fed Ldlr−/− mice diets containing 10% (calories) palm oil (PO) and 0.2% cholesterol, supplemented with an additional 10% of calories as PO, fish oil (FO), echium oil (EO, containing 18:4 n-3), or borage oil (BO, containing 18:3 n-6). Infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 60 publications
2
63
0
1
Order By: Relevance
“…147 Alternatively, chemical compounds such as rapamycin, AICAR, resveratrol, celastrol, ezetimibe, and polyunsaturated fatty acids, are known to induce autophagy. 105,[148][149][150][151][152] Although a hypocaloric diet and these compounds regulate not only autophagy but also various cellular responses, they are reported to ameliorate inflammation. [150][151][152][153][154][155] Thus, pharmacological modulation of autophagy may provide a potential therapy for inflammasome-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…147 Alternatively, chemical compounds such as rapamycin, AICAR, resveratrol, celastrol, ezetimibe, and polyunsaturated fatty acids, are known to induce autophagy. 105,[148][149][150][151][152] Although a hypocaloric diet and these compounds regulate not only autophagy but also various cellular responses, they are reported to ameliorate inflammation. [150][151][152][153][154][155] Thus, pharmacological modulation of autophagy may provide a potential therapy for inflammasome-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory properties of DHA and EPA also include the inhibition of the NOD-like receptor protein 3 (NLRP3) inflammasome activation in macrophages [108,109]. This effect is mediated in vitro and in vivo by GPR120 and GPR40 receptors, their downstream protein β-arrestin-2 [109], and autophagy induction [110]. Interestingly, pro-inflammatory properties of SFAs (PA) are confirmed in the inflammasome-related inflammation.…”
Section: Macrophagesmentioning
confidence: 99%
“…The deficiency of G‐protein‐coupled receptor 120 (GPR120) and GPR40 predominantly suppresses the influence of DHA in NLRP3 inflammasome activation, and β ‐arrestin 2, a protein downstream of GPR120, can directly interact with NLRP3 or NLRP1b but not NLRC4 or AIM2, which may explain the exclusive inhibition of NLRP3 and NLRP1b inflammasome activation . A recent study reported that ω ‐3 UFAs in dietary PUFAs alleviated NLRP3 inflammasome activation . In addition, derivatives of PUFAs generated via the lipoxygenase (LOX) and cyclooxygenase (COX) pathways may also partially influence inflammatory responses .…”
Section: Metabolic Reprogramming Controls Inflammasome Activationmentioning
confidence: 99%
“…75 A recent study reported that x-3 UFAs in dietary PUFAs alleviated NLRP3 inflammasome activation. 76 In addition, derivatives of PUFAs generated via the lipoxygenase (LOX) and cyclooxygenase (COX) pathways may also partially influence inflammatory responses. [77][78][79] It has been shown that 15-LOX metabolites of a-linolenic acid (ALA, x-3 UFAs) inhibited NLRP3 inflammasome activation in a peroxisome proliferator-activated receptor-c (PPAR-c)-dependent manner, which in turn induced apoptosis through suppressing autophagy.…”
Section: Fatty Acid Synthesis and Inflammasome Activationmentioning
confidence: 99%